2023
DOI: 10.1101/2023.01.23.525198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematically characterizing the roles of E3-ligase family members in inflammatory responses with massively parallel Perturb-seq

Abstract: E3 ligases regulate key processes, but many of their roles remain unknown. Using Perturb-seq, we interrogated the function of 1,130 E3 ligases, partners and substrates in the inflammatory response in primary dendritic cells (DCs). Dozens impacted the balance of DC1, DC2, migratory DC and macrophage states and a gradient of DC maturation. Family members grouped into co-functional modules that were enriched for physical interactions and impacted specific programs through substrate transcription factors. E3s and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…We next asked if SC-VAE can capture how perturbations are related to each other such that learned perturbation map is biologically relevant [23]. To test this, we relied on the well-established assumption that perturbations in genes encoding members of the same protein complex should lead to similar phenotypes an thus more similar cell profiles [6, 8]. Accordingly, We adapted previous methodology, using the CORUM complex database [24] and the following process:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next asked if SC-VAE can capture how perturbations are related to each other such that learned perturbation map is biologically relevant [23]. To test this, we relied on the well-established assumption that perturbations in genes encoding members of the same protein complex should lead to similar phenotypes an thus more similar cell profiles [6, 8]. Accordingly, We adapted previous methodology, using the CORUM complex database [24] and the following process:…”
Section: Resultsmentioning
confidence: 99%
“…Some sources of technical noise are those common to all scRNA-seq studies, such as the sequencing depth and count over-dispersion, but others are specific to the perturbation context. For example, the capture rate of the guide RNA may be noisy, and therefore the association of a single cell to a perturbation may have some error [8]. Second, guide expression in a cell does not not necessarily mean that the cell has been genetically perturbation, because of varying efficiency rates of the Cas9 enzyme and the time delay from genetic perturbation to an effect on the target protein [9, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell screens link genetic perturbations to genome-wide transcriptional phenotypes. Previous studies 39,40 have identified shared gene programs that are commonly altered by multiple perturbations. If multiple distinct perturbations (defining a perturbation module) affect a common set of genes (defining a gene program), the rationale is that these perturbed genes/enhancers may contribute to breast cancer through shared mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…First, to identify perturbation modules that yield similar transcriptional phenotypes, we combined cells with a given regulatory element perturbed as a ‘meta-cell’ and clustered meta-cells by expression similarity 40 . We first filtered out lowly expressed genes and focused on the top 1,000 highly variable genes.…”
Section: Resultsmentioning
confidence: 99%
“…Intuitively, a physical interaction between two proteins suggest that they might participate in a shared biomolecular pathway or complex. Thus, perturbations of genes coding for physically interacting proteins might lead to similar effects [40]. For each perturbation x, ϕ x is a node embedding of x in the PPI network, such as node2vec [41].…”
Section: Methodsmentioning
confidence: 99%